Врахування екологічних обмежень при моделюванні розвитку вугільної промисловості - Makarov V.M.; Kaplin M.I.; Perov M.O. (General Energy Institute of the National Academy of Sciences of Ukraine, 2019)
The article was prepared within the framework of project financed by the budget program “Support for the Development of Priority Areas of Scientific Research” (CCPCC 6541230).Under conditions when the coal industry needs a radical upgrade, and its development is directly dependent on the successful solution of problems of coal seam degassing and fight against gas-dynamic phenomena, the task of creating mathematical models and software tools for optimizing the technological development of coal industry with regard for modern environmental constraints becomes quite topical.The proposed mathematical model of technological development of coal industry takes into account the environmental consequences of mines work by connecting the volumes of coal production with the volumes of coal-mine methane extraction, the required equipment for its utilization, and the amount of capital expenditure for such equipment. Taking this expenditure into account under conditions of growing of increased environmental requirements to the operation of coal industry is a necessary element in forecasting its development, in particular, the financial support for modernization programs.The solution of problem of optimizing the technological development of coal industry with regard for the use of mine methane utilization facilities includes multiple options for re-equipping mines with equipment of the new technical level, which maximizes the total volume of own coal production at its cost, which ensures the competitiveness of industry in the world market.The software implementation of model made it possible to determine the efficient technologies and optimum complete set of cleaning complexes for the re-equipment of mines, provided that they achieve the maximum production volumes and ensure environmental safety.The modernization of mines on the territory under control of the Ukrainian authorities can be carried out by 2025. To this end, it is necessary to attract 2.6 billion UAH investment funds for the purchase of mining equipment, including 240 million UAH for degassing equipment. Coal production will increase from 42 million tons in 2020 to 47 million tons in 2025. Further, due to the depletion of coal reserves, there will be a gradual reduction of the mine fund, which will lead to a decrease in production to 32.4 million tons in 2040.At all mines where methane content exceeds the standards, it is necessary to install degassing equipment. This will reduce methane emissions by 275 million m3 in 2020, 550–590 million m3 in 2025–2035, and 400 million m3 in 2040.